Peningkatan Keterampilan Menulis Bahasa Jawa dengan Metode CIRC melalui Media Komik Strips Siswa Kelas V di SD Negeri 03/04 Margoyoso - Wahyuni, Selvy; Hanik, Elya Umi (Lembaga Yasin AlSys, 2021)
This study aims to improve writing skills in Javanese using the CIRC (Cooperative Integrated Reading and Compotition) method. The low ability to write Javanese is considered difficult for students, as a result, students are passive in learning. The CIRC Method Through STRIPS Comic Media is expected to be an alternative for learning to write Javanese. The type of research used is Classroom Action Research using one cycle, in the initial conditions, which initially only averaged 13 or 52.86% of students who had writing skills, in the first cycle the score increased to 19 or 74.71% of students. The impact of research using the CIRC method of learning through STRIPS Comic Media can improve the writing skills of the fifth grade students of Margoyoso State Elementary School.